House Rehabilitation as Poverty Elimination Form - Hikmawati, Eny; Gutomo, Tri (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This research was done to know Kulonprogo Regency government policy on poverty elimination through houses rehabilitation (PBR). The research used qualitative-descriptive approach, using informants (program commitees, poor families beneficiaries, public figures), observation as data resources. Data was analysed through qualitative-descriptive technique. The research showed that houses rehabilitation program implemented in Kulonprogo Regency proved successfully on eliminating poverty, especially in providing houses for poor families. Houses rehabilitation implemented transparantly through submiting proposal, verification agreement for program beneficiary. The success of home rehabilitation could not be rid off regent commitment on his decree to cut 2.5 percent of each moslem local civil servant salary to fund the rehabilitation (managed by Bazda), and whole and active participation and sinergy support from related agencies, subdistrict leaders, entreprenur, funding institution, and community mutual cooperation as social capital. It recommended that home rehabilitation can be diseminated in other regions commited on poverty elimination